Presentation of Marginality from the Indigenous Community in Rajan Mukarung’s Hetchhakupa - Rai, Bidur (JODEM: Journal of Language and Literature, 2023)
This article analyzes how Rajan Mukarung’s novel Hetchhakuppa represents the indigenous people as marginalized indigenous characters from the critical perspective of subaltern studies as furthered in postcolonial India to rewrite the social history of the post-independence period. The major theorists, beginning with Ranjit Guha to Gayatri Chakravarti Spivak, state that the people at the bottom tend to get misrepresented and termed inaccessible for the people at the top. However, this study contends that J. Magio aids in our comprehension of the notion that individuals express their voice through artistic creations. Mukarung’s Hetchhakuppa focuses on the cultural and indigenous identity of the characters, lending a voice to their suffering and marginalization. It implies that indigenous but marginal people are silenced due to the context of socio-political structure, so their voices are unheard and ignored. Thus, this paper concludes that the contemporary Nepali fiction Hetchhakuppa depicts the unheard characters.